Stylistic Analysis Of Language Style And Social Meaning In Movie “Woman Of The Hour” By Anna Kendrick - Yuni Ratna Purwaningsih; Rosalia Floriani; Nurul Istiqomah; Arin Mantara Anggawirya; Evelin Giovani (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the language style and social meaning in Woman of the Hour directed by Anna Kendrick. The research uses a descriptive qualitative method with a stylistic approach to identify the forms of language style used in the movie and to interpret their social meanings. The data were collected from dialogues, expressions, and symbolic elements appearing throughout the film. The data analysis was conducted through data reduction, classification, interpretation, and conclusion drawing based on stylistic theory and social meaning analysis. The findings reveal that the film employs a realistic, manipulative, and psychologically tense language style to portray power imbalances within a patriarchal society. Conversational style, manipulative language, silent communication, and symbolism such as the show’s script, Polaroid cameras, and studio lighting function not only as aesthetic elements but also as media for social criticism regarding the objectification of women, psychological manipulation, and society’s failure to recognize danger. The film illustrates how women are often expected to maintain politeness and social comfort even in threatening situations. This study implies that stylistic analysis can help reveal the relationship between language, symbolism, and social conditions in films, especially concerning gender issues and violence against women. Furthermore, this research is expected to increase public awareness of social manipulation and the importance of respecting women’s intuition and sense of safety.